The beneficial effect of CO2 in the low temperature synthesis of high quality carbon nanofibers and thin multiwalled carbon nanotubes from CH4 over Ni catalysts - Corthals, Steven; Van Noyen, Jasper; Geboers, Jan; Vosch, Tom; Liang, Duoduo; Ke, Xiaoxing; Hofkens, Johan; Van Tendeloo, Gustaaf; Jacobs, Pierre; Sels, Bert (Carbon (New York), 2012)
A low temperature chemical vapor deposition method is described for converting CH₄ into high-quality carbon nanofibers (CNFs) using a Ni catalyst supported on either spinel or perovskite oxides in the presence of CO₂. The addition of CO₂ has a significant influence on CNF purity and stability, while the CNF diameter distribution is significantly narrowed. Ultimately, the addition of CO₂ changes the CNF structure from fishbone fibers to thin multiwalled carbon nanotubes. A new “in situ” cooling principle taking into account dry reforming chemistry and thermodynamics is introduced to account for the structural effects of CO₂.